Epidemiology of sepsis and its various characteristics in a tertiary care adult-multidisciplinary ICU in South India: a retrospective study - Tharappel Jalal, Hussain Khan; Thomas, Teju P.; George, Alfy Ann; Mohammed, Hamadan (International Journal of Research in Medical Sciences, 2020)
Background: The incidence of sepsis is increasing, especially in elderly populations with more comorbidities. It is now estimated that sepsis is a leading cause of mortality and critical illness worldwide. The Epidemiological data regarding sepsis, septic shock and organ involvement is mainly from western literature. Data from India, especially south India, are less when compared to western data. In this background authors conducted a retrospective study in tertiary care hospital in south India. Objectives of the study was epidemiology of sepsis and its various characteristics in a tertiary care adult-Multi disciplinary ICU in South India. Methods: This study was a retrospective observational study, conducted during the time period of June 2016 and May 2017. The study population was patients above 18 yrs admitted in MDICU with sepsis. The study was conducted in a tertiary care adult -Multidisciplinary ICU in South India. Various characteristics like age group, comorbidities, organ involvement, septic shock, sofa score, need for ventilatory support, RRT support and outcome data was collected. Results: In this study, 497 patients who satisfied the Surviving Sepsis Campaign guidelines were included. The majority of the patients (59.8%) were male; the majority was above 60 yr (range 18 to 92 yr). 76.3% Patients had comorbid disease. Hypertension was the most common co-morbid (62%) followed by diabetes mellitus (51.3%). Chronic Kidney Disease was found in 132 patients (26.6%) and Coronary artery disease in 121 patients (24.3%). 186 patients (46.5%) had single organ involvement 140(35%) patients had 2 organ involvement. 74(18.5%) patients had more than 2 organ involvement. Septic shock was found in 155 patients (31.2%). Renal involvement was the most common organ involvement found in 279 patients(59.9%). Most common source for sepsis was the respiratory system found in 230 patients (46.3%), followed by urinary tract infection in 117 patients (23.5%). The study shows a significant association between SOFA score and mortality (p-value 0.001) 52% of mortality happened in group of patients with SOFA score more than 15 and mortality was 28 % in group with a SOFA score of 10-15. Conclusions: In this retrospective study of sepsis, authors found that the most common source of sepsis was pneumonia (46.3%) followed by urinary tract infection (23.5%). Majority of the patients had one organ involvement (46.5%). Among the organ involvement, Acute Kidney injury was the most common organ involvement (56.1%) followed by septic shock (31.2%) and respiratory support (29.6%). Mortality in this study was higher with higher SOFA score.